Model development for coffee processing plant location selection by using AHP method: Case of Guji Zone, Ethiopia - Fasika Bete Georgise; Boru Bedeya Jarso; Alemayehu Tesfaye Mindaye (Cogent Business & Management, 2020)
It is very difficult to find a suitable location for a coffee processing plant from many alternatives. This research-developed a model by Analytic hierarchy pair wise that gives full information for a coffee processing plant to select a suitable location from alternatives as its objective. The main location factors were analyzed by the Analytic Hierarchy Process (AHP) wise method to rank candidate alternative locations.The questionnaire analysis mainly used Statistical Packaging Social Software (SPSS) and AHP method for weighting and ranking alternative locations according to the evaluation of location criteria priority values. The discussion addressed as the misallocation has an impact on selecting a suitable location before, and it is good to follow this developed model. It is inevitable for the society to update with the growth model and generally pre-coffee processing plant owners are facing problems in selecting a suitable location from alternatives in a Guji Zone. The proposed model has three main sequential stages that focus on reducing the time to decide on a new suitable location. Thus, it reduces the effort for searching and deciding the best location for pre-coffee processors. The result is summarized in the framework model that can lead users to understand the current status and the trend concerning the models and factors used in the primary coffee processing plant location selection decision. This research has proposed a suitable solution for the location problems. Finally, the recommendation was given to coffee processing actors and responsible government offices.
Keywords: 650; coffee; coffee processing plant; location; location factors; AHP method; model